How to use good Japanese (Japan, 1979)
This book consists of the text and its references. In the first 15 lessons, the text proper is written in Romaji. In and after lesson 16, the contents of this book have been mostly abridged from the " Nihongo rio Hanshikata",...
Keywords: Japanese language; Textbooks for foreign speakers,English